Tumor necrosis factor-α-treated human adipose-derived stem cells enhance inherent radiation tolerance and alleviate in vivo radiation-induced capsular contracture - Chanutchamon Sutthiwanjampa; Seung Hyun Kang; Mi Kyung Kim; Jin Hwa Choi; Han Koo Kim; Soo Hyun Woo; Tae Hui Bae; Woo Joo Kim; Shin Hyuk Kang; Hansoo Park (Journal of Advanced Research)
Introduction: Post-mastectomy radiotherapy plays a crucial role in breast cancer treatment but can lead to an inflammatory response causing soft tissue damage, particularly radiation-induced capsular contracture (RICC), impacting breast reconstruction outcomes. Adipose-derived stem cells (ADSCs), known for their regenerative potential via paracrine capacity, exhibit inherent radiotolerance. The influence of tumor necrosis factor-alpha (TNF-α) on ADSCs has been reported to enhance the paracrine effect of ADSCs, promoting wound healing by modulating inflammatory responses. Objective: This study investigates the potential of TNF-α-treated human ADSCs (T-hASCs) on silicone implants to alleviate RICC, hypothesizing to enhance suppressive effects on RICC by modulating inflammatory responses in a radiation-exposed environment. Methods: In vitro, T-hASCs were cultured on various surfaces to assess viability after exposure to radiation up to 20 Gy. In vivo, T-hASC and non-TNF-α-treated hASC (C-hASCs)-coated membranes were implanted in mice before radiation exposure, and an evaluation of the RICC mitigation took place 4 and 8 weeks after implantation. In addition, the growth factors released from T-hASCs were assessed. Results: In vitro, hASCs displayed significant radiotolerance, maintaining consistent viability after exposure to 10 Gy. TNF-α treatment further enhanced radiation tolerance, as evidenced by significantly higher viability than C-hASCs at 20 Gy. In vivo, T-hASC-coated implants effectively suppressed RICC, reducing capsule thickness. T-hASCs exhibited remarkable modulation of the inflammatory response, suppressing M1 macrophage polarization while enhancing M2 polarization. The elevated secretion of vascular endothelial growth factor from T-hASCs is believed to induce macrophage polarization, potentially reducing RICC. Conclusion: This study establishes T-hASCs as a promising strategy for ameliorating the adverse effects experienced by breast reconstruction patients after mastectomy and radiation therapy. The observed radiotolerance, anti-fibrotic effects, and immune modulation suggest the possibility of enhancing patient outcomes and quality of life. Further research and clinical trials are warranted for broader clinical uses.